NURCHOLISH MADJID’S QURAN-BASED CONCEPT OF CRITICAL PLURALISM - Tasrif, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2016)
Pluralism is one theme of Islamic thought of Nurcholish widely debated by Indonesian Muslims. Nurcholish built his thought by referring to verses of the Quran. Nurcholish’s thought had sparked sharp controversy. In one hand, Nurcholish is regarded as a public figure who can provide the basics of the remedies for Indonesian nation which is religiously and culturally plural. On other hand, Nurcholish is a prominent denier and destroyer of Islamic theology. Based on the background, this article explores the socio-historical background of Nurcholish’s support on the concept of pluralism, its fundamental structures, its Quranic bases, and its distinctiveness compared to ideas of other thinkers. Pluralism according to Nurcholish is understood as a value system which looks positively at plural realities and acts also positively on the basis of the realities. Pluralism in Nurcholish’s explanation includes notion of pluralism in many fields of studies: cosmological-ontological, social, cultural, political, and religious. Pluralism of Nurcholish rests on beliefs about God and human. Two basic beliefs that become foundations of Nurcholish’s concept of pluralism have implications to uniqueness of his concept of religious pluralism.